2013
DOI: 10.1161/circresaha.111.300104
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoproteins Inhibit Vascular Endothelial Inflammation by Increasing 3β-Hydroxysteroid-Δ24 Reductase Expression and Inducing Heme Oxygenase-1

Abstract: Rationale: Lipid-free apolipoprotein (apo) A-I and discoidal reconstituted high-density lipoproteins (rHDL) containing apoA-I, (A-I)rHDL, inhibit vascular inflammation by increasing 3β-hydroxysteroid-Δ24 reductase (DHCR24) expression. Objective: To determine whether the lipid-free apoA-I–mediated and (A-I)rHDL-mediated increase in DHCR24 expression induces the cytoprotective and potentially cardioprotective enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 51 publications
3
48
0
Order By: Relevance
“…Furthermore, it has been documented that in cultured endothelial cells, incubation with HDLs prevented NF-κβ activation, movement of p65 to the nucleus, and expression of NF-κβ target genes in response to TNFα (Xia et al 1999;Park et al 2003;Kimura et al 2006;McGrath et al 2009). The basal molecular mechanisms of the beneficial effects of HDL on endothelial inflammation are dependent on an increase in the expression of 3β-hydroxysteroid-Δ24 reductase that results in activation of PI3K and downstream activation of eNOS and heme oxygenase-1 (HO-1) (McGrath et al 2009;Wu et al 2013). Specific knockdown of SR-BI or S1P1 receptor by treatment of human endothelial cells with small interfering RNAs against SR-BI and PDZK1 or S1P1, respectively, markedly reduced the ability of HDLs to inhibit VCAM-1 expression and NF-κβ activation (Kimura et al 2006;Wu et al 2013), suggesting that both receptors may be critical for the anti-inflammatory endothelial actions of HDLs.…”
Section: Suppression Of Monocyte Extravasationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been documented that in cultured endothelial cells, incubation with HDLs prevented NF-κβ activation, movement of p65 to the nucleus, and expression of NF-κβ target genes in response to TNFα (Xia et al 1999;Park et al 2003;Kimura et al 2006;McGrath et al 2009). The basal molecular mechanisms of the beneficial effects of HDL on endothelial inflammation are dependent on an increase in the expression of 3β-hydroxysteroid-Δ24 reductase that results in activation of PI3K and downstream activation of eNOS and heme oxygenase-1 (HO-1) (McGrath et al 2009;Wu et al 2013). Specific knockdown of SR-BI or S1P1 receptor by treatment of human endothelial cells with small interfering RNAs against SR-BI and PDZK1 or S1P1, respectively, markedly reduced the ability of HDLs to inhibit VCAM-1 expression and NF-κβ activation (Kimura et al 2006;Wu et al 2013), suggesting that both receptors may be critical for the anti-inflammatory endothelial actions of HDLs.…”
Section: Suppression Of Monocyte Extravasationmentioning
confidence: 99%
“…The basal molecular mechanisms of the beneficial effects of HDL on endothelial inflammation are dependent on an increase in the expression of 3β-hydroxysteroid-Δ24 reductase that results in activation of PI3K and downstream activation of eNOS and heme oxygenase-1 (HO-1) (McGrath et al 2009;Wu et al 2013). Specific knockdown of SR-BI or S1P1 receptor by treatment of human endothelial cells with small interfering RNAs against SR-BI and PDZK1 or S1P1, respectively, markedly reduced the ability of HDLs to inhibit VCAM-1 expression and NF-κβ activation (Kimura et al 2006;Wu et al 2013), suggesting that both receptors may be critical for the anti-inflammatory endothelial actions of HDLs. Corresponding with the possible involvement of the S1P1 receptor, the inhibitory activity of HDLs on the expression of endothelial cell adhesion molecules has been proposed to be a function of biologically active lysosphingolipids carried by HDL particles (Nofer et al 2003;Kimura et al 2006).…”
Section: Suppression Of Monocyte Extravasationmentioning
confidence: 99%
“…119,121,122 More recent studies indicate that the interaction of HDL with SR-BI on endothelial cells increases the expression of heme oxygenase-1 by activation of PI3K/Akt through 3β-hydroxysteroid-∆24 and that this may play an important role in the suppression of endothelial inflammation by HDLs. 122, 123 Although interactions between endothelial cells and monocytes require the expression of adhesion molecules on both cell types, the effect of HDLs on monocytic adhesion molecules has been less extensively investigated. There is one study showing that treatment of human monocytes with native HDL, reconstituted HDL, or apoA-I reduced the expression and activation of the monocyte adhesion molecule CD11b.…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
“…Wu et al . also demonstrated that HDL decreases collar‐induced endothelial adhesion molecule expression and reduces intima/media neutrophil infiltration by inducing HO‐1 expression; however, down‐regulation of HO‐1 abolishes the protective effects of HDL 38. In addition, Vanella et al .…”
Section: Discussionmentioning
confidence: 96%